Home waters : a chronicle of family and a river - Maclean, John N. (Custom House, 2021)
"A universal story about the power of place to shape families: In the spirit of his father's beloved classic A River Runs Through It, comes John N. Maclean's meditation on fly fishing and life along Montana's Blackfoot River, where four generations of Macleans have fished, bonded, and drawn timeless lessons from its storied waters"--